An anthology of the distinguished achievements in a science and technique. Part 24: Subjugation of earthly dry land and world ocean - M.I. Baranov (National Technical University "Kharkiv Polytechnic Institute", 2015)
A short essay of world history of subjugation and study by humanity of earthly continental dry land and enormous marine spaces of Earth is presented.